2002
DOI: 10.1207/s15327922par0202_01
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Rough and Tumble: Low-Income Fathers' Interactions and Children's Cognitive Development at 24 Months

Abstract: SYNOPSISObjective. The purpose of this investigation was to explore associations between father-child interactions and children's cognitive status in an underrepresented group of low-income, ethnically diverse families. Design. Participants were 65 inner-city fathers and their 24-month-old children (34 boys, 31 girls). Father-child interactions were videotaped for 10 min at home during semistructured free play, and mental scale scores on the Bayley Scales of Infant Development were obtained on children. The qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
140
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(153 citation statements)
references
References 73 publications
9
140
1
3
Order By: Relevance
“…Results of this study support the findings of previous studies (Dunst, 1985;Gleason, 1975;Flippin & Crais, 2011;Middleton, 1995;Pellegrini, et al, 1985;Pleck & Masciadrelli, 2004;Shannon et al, 2002;Sloper, 1999;Sloper & Turner, 1993;Tannock, 1988) which prove that the relationship of father involvement with wellbeing of children with special needs is positive and significant. In the context of the father involvement against well-being of children with special needs, the father involvement clearly plays a large role in influencing the well-being of children with special needs widely not only in child development.…”
Section: Resultssupporting
confidence: 91%
“…Results of this study support the findings of previous studies (Dunst, 1985;Gleason, 1975;Flippin & Crais, 2011;Middleton, 1995;Pellegrini, et al, 1985;Pleck & Masciadrelli, 2004;Shannon et al, 2002;Sloper, 1999;Sloper & Turner, 1993;Tannock, 1988) which prove that the relationship of father involvement with wellbeing of children with special needs is positive and significant. In the context of the father involvement against well-being of children with special needs, the father involvement clearly plays a large role in influencing the well-being of children with special needs widely not only in child development.…”
Section: Resultssupporting
confidence: 91%
“…The use of these responsive verbal strategies by mothers has been linked to achievement of earlier language milestones and better cognitive and social-emotional outcomes in studies of children who are typically developing as well as children who are at-risk for poor outcomes (Landry, Swank, & Smith, 2006;Tamis-LeMonda, Bornstein, & Baumwell, 2001). Responsive fathering also is a strong predictor of better emotional regulation, cognition, and language development for both children with typical development and those who are at-risk (Shannon, Tamis-LeMonda, London, & Cabrera, 2002;Tamis-LeMonda, Shannon, Cabrera, & Lamb, 2004). Maternal responsiveness has also been shown to predict language development in children with developmental disorders, including developmental delay and Fragile X syndrome (Brady, Marquis, Fleming, & McLean, 2004;Brady, Warren, Fleming, Keller, & Sterling, 2014;Hauser-Cram, Warfield, Shonkoff, & Krauss, 2001;Landry, Smith, & Swank, 2006).…”
Section: Parent Responsivenessmentioning
confidence: 99%
“…Children may benefit from interacting with multiple caregivers, providing them with a diversity of stimulation (Gleason, 1975;. High-quality father-child interactions that are responsive, stimulating, and engaging have been found to positively predict better cognitive and language outcomes for young children during the first 3 years of life (Roopnarine, 2004;Shannon, Tamis-LeMonda, London, & Cabrera, 2002;. In one of the few studies to consider the contributions of father language input to early child language development, Pancsofar and Vernon-Feagans (2006) found that dual-earner fathers' vocabulary during triadic motherfather-child free-play interactions made a significant and unique contribution to children's expressive language development at 36 months of age, beyond the contribution of mother language input.…”
Section: Parental Language Inputmentioning
confidence: 99%